Hypertonicity during a rapid rise in D-glucose mediates first-phase insulin secretion - Kamat, Varun; Sweet, Ian R. (Frontiers in Endocrinology, 2024)
Biphasic insulin secretion is an intrinsic characteristic of the pancreatic islet and has clinical relevance due to the loss of first-phase in patients with Type 2 diabetes. As it has long been shown that first-phase insulin secretion only occurs in response to rapid increase in glucose, we tested the hypothesis that islet response to an increase in glucose is a combination of metabolism plus an osmotic effect where hypertonicity is driving first-phase insulin secretion. Experiments were performed using perifusion analysis of rat, mouse, and human islets. Insulin secretion rate (ISR) and other parameters associated with its regulation were measured in response to combinations of D-glucose and membrane-impermeable carbohydrates (L-glucose or mannitol) designed to dissect the effect of hypertonicity from that of glucose metabolism. Remarkably, the appearance of first-phase responses was wholly dependent on changes in tonicity: no first-phase in NAD(P)H, cytosolic calcium, cAMP secretion rate (cAMP SR), or ISR was observed when increased D-glucose concentration was counterbalanced by decreases in membrane-impermeable carbohydrates. When D-glucose was greater than 8 mM, rapid increases in L-glucose without any change in D-glucose resulted in first-phase responses in all measured parameters that were kinetically similar to D-glucose. First-phase ISR was completely abolished by H89 (a non-specific inhibitor of protein kinases) without affecting first-phase calcium response. Defining first-phase ISR as the difference between glucose-stimulated ISR with and without a change in hypertonicity, the peak of first-phase ISR occurred after second-phase ISR had reached steady state, consistent with the well-established glucose-dependency of mechanisms that potentiate glucose-stimulated ISR. The data collected in this study suggests a new model of glucose-stimulated biphasic ISR where first-phase ISR derives from (and after) a transitory amplification of second-phase ISR and driven by hypertonicity-induced rise in H89-inhibitable kinases likely driven by first-phase responses in cAMP, calcium, or a combination of both.